Funkties van tekenen. - Fuchs, R.H (Otterlo : Rijksmuseum Kröller-Müller, 1975)
LeWitt, Sol ; Strycken, Peter ; Beuys, Joseph ; Broodthaers, Marcel ; Darboven, Hanne ; Penck, A.R. ; Flavin, Dan ; Nauman, Bruce ; Long, Richard ; Judd, Don ; Panamarenko ; André, Carl ; Dekkers, Ad ; Kelly, Ellsworth ; Marden, Brice ; de Maria, Walter ; Martin, Agnes ; Raetz, Markus ; Twombly ; Visser, CArel ; etc.
Funkties van tekenen / Functions of Drawing, Rijksmuseum Kröller-Müller, Otterlo, 25 mei tot 4 augustus 1975
boek